Expression and Effect of Inhibition of the Ubiquitin-Conjugating Enzyme E2C on Esophageal Adenocarcinoma - Jules Lin (Neoplasia: An International Journal for Oncology Research, 2006)
Ubiquitin-dependent proteolysis of cyclins plays a critical role in cell cycle progression and tumorigenesis. We examined the expression of ubiquitin-conjugating enzyme E2C (UBE2C) during progression from Barrett's metaplasia to esophageal adenocarcinoma (EA) and the effects of targeting this enzyme on EA-derived cell lines. Using oligonucleotide microarrays UBE2C expression was elevated in 73% (11 of 15) of EAs relative to Barrett's metaplasia. Tissue microarray showed elevated UBE2C in 70% (7 of 10) of dysplastic samples and in 87% (58 of 67) of tumors relative to metaplastic samples. Transfection of dominant-negative UBE2C into Seg-1 cells decreased proliferation (P = .04) and increased mitotic arrest compared to vector controls (63.5% vs 6.8%; P < .001). Transfection of UBE2C small interfering RNA also caused inhibiton of cell proliferation and distortion of the cell cycle, with maximal increase of G2 cells (155% of mock cells) at 72 hours and of S-phase cells (308% of mock cells) at 24 hours. Treatment of Seg-1 cells with the proteasome inhibitor MG-262 (1 nM- µM) showed decreased proliferation (P = .02). EA-derived cells expressing UBE2C are sensitive to treatment with MG-262 and to silencing of UBE2C, suggesting that patients with EAs overexpressing UBE2C may benefit from agents targeting this ubiquitin-conjugating enzyme.